2014
DOI: 10.1021/am5026243
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Functionalized Gold Nanoparticles As Photoresponsive Nanoplatform for Co-Drug Delivery

Abstract: Various platforms have been developed as innovative nanocarriers to deliver therapeutic agents to the diseased sites. Multifunctional surface modification allows an enhanced recognition and uptake of drug carriers by targeted cells. However, the development of drug resistance in some tumor cells plays a major role in the failure of chemotherapy. Drugs given in combination, called multidrug delivery approach, was designed to improve the therapeutic efficacy and has become an increasingly used strategy that is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 67 publications
1
77
0
Order By: Relevance
“…Targeting ligands [56][57][58][59][60] may be modified onto the AuNP surface to specifically deliver therapeutic cargos into tissues and organs. Recently, tumor-targeted mesoporous silicaencapsulated GNRs (GNRs@mSiO 2 ) for chemotherapy and photothermal therapy (PTT) have been developed by Shen et al 61 In this study, RGD peptides, a targeting ligand for α v β 3 integrin receptors that are known to overexpress on several cancer cells, were conjugated to the terminal groups of PEG on GNRs@mSiO 2 (namely, pGNRs@mSiO 2 -RGD).…”
Section: Surface Functionalization Of Aunpsmentioning
confidence: 99%
“…Targeting ligands [56][57][58][59][60] may be modified onto the AuNP surface to specifically deliver therapeutic cargos into tissues and organs. Recently, tumor-targeted mesoporous silicaencapsulated GNRs (GNRs@mSiO 2 ) for chemotherapy and photothermal therapy (PTT) have been developed by Shen et al 61 In this study, RGD peptides, a targeting ligand for α v β 3 integrin receptors that are known to overexpress on several cancer cells, were conjugated to the terminal groups of PEG on GNRs@mSiO 2 (namely, pGNRs@mSiO 2 -RGD).…”
Section: Surface Functionalization Of Aunpsmentioning
confidence: 99%
“…This composition was shown to have more than a 4-fold higher action. In another study, aptamer-functionalized GNPs were codelivered with two different anticancer drugs, achieving an improvement in drug efficacy (Shiao et al 2014). Huang et al (2008) demonstrated that ∼80 aptamers could be linked covalently to the surface of Au-Ag nanorods using thiolated functional groups on the aptamers.…”
Section: Aptamer-conjugated Nanoparticlesmentioning
confidence: 99%
“…AS1411 functionalized AuNPs have been applied to targeted deliver chemotherapeutic doxorubicin in tumor tissues where exist higher concentrations of reductive agents such as glutathione than normal ones for increasing release of drugs, and subsequently reducing cell viability of breast cancer, cervical cancer and uveal melanoma cell lines. 53,54 Anti-His and anti-GST aptamers conjugated to citrate reduced AuNPs are able to selectively deliver various His or GST tagged proteins into varieties of cell types in vitro and in vivo for protein based tumor treatment. 55 Meanwhile, the aptamer functionalized platform for drug delivery still can combine with other methods to improve the e±cacy of chemotherapy.…”
Section: Aunps-based Drug Deliverymentioning
confidence: 99%